PENEGAKAN HUKUM TERHADAP PELAKU YANG MEMBAYAR UPAH PEKERJA/BURUH DI BAWAH UPAH MINIMUM DI WILAYAH PROVINSI RIAU - Hengki Rafles Rajagukguk; Davit Rahmadan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
Wage is the right of the Worker/Labourer that is received and expressed inthe form of money as a reward from the Employer or employer to theWorker/Labourer which is determined and paid according to a work agreement.agreements, or laws and regulations, including allowances forWorkers/Labourers and their families for a job and/or service that has been orwill be performed. In the provision of wages for workers/labor by employers,violations often occur. One of the violations committed by employers is to giveworkers/laborers wages below the minimum wage. whereas in Article 88 Eparagraph 2 of Law Number 11 of 2020 concerning Job Creation it is clearlystated that; “Entrepreneurs are prohibited from paying wages lower than theminimum wage, and the sanctions are contained in article 185. From 2020 to2022 there were 10 complaints that went to the Riau provincial manpower officesupervisor regarding wage violations.The purpose of this study is to find out howthe law enforcement process is carried out by labor inspectors against wageviolations committed by employers, what are the obstacles to labor inspectors,and to know the efforts made to overcome the wage problem. In addition, thisstudy also examines the role of labor law in solving industrial relations problems.From the results of the research discussion, it can be concluded that theposition of labor law in the Indonesian national legal system can theoretically beseparated into 3 fields, namely the administrative field, the civil field, and thecriminal field. But in practice it must be run simultaneously because it relates toone another. The legal relationship carried out by workers/laborers withemployers is included in the field of civil law. However, during the process ofmaking, implementing, and ending the relationship, the government is supervisedin order to carry out its 3 functions. If during these processes there are violations(not in accordance with applicable regulations), then criminal sanctions can beapplied.Keywords: Law Enforcement – Wages of workers/laborers below the minimumwage – Labor inspectors - Riau Province